Turkish speech-language therapists' perceptions and experiences of augmentative and alternative communication - Yaşa, İbrahim Can; Tokalak, Selin (The European Research Journal, 2023)
Objectives: In this study, it is aimed to reveal what extent speech and language therapists (SLT) working in Turkey used augmentative and alternative communication (AAC) systems in their working area. For this purpose, it was investigated how they perceive AAC in terms of its scope and role; ACC applications within the scope of interventions for communication, language and speech disorders; best practice insights on AAC; what factors are seen as facilitating or limiting the implementation of AAC within the scope of intervention and suggestions for providing the best practice for AAC. Methods: Phenomenology, one of the qualitative research methods, was used in the study. The subject of the study is the opinions of SLTs working in Turkey on their clinical practices and thoughts on the use of AAC. The study group consists of 15 SLTs from Turkey and determined by using maximum diversity sampling method. The semi-structured interview forms were used in which SLTs’ views, suggestions and expectations about AAC applications in the service delivery as a data collection tool. The obstacles and difficulties in these applications were discussed. Content analysis was used and also carried out using the qualitative data analysis program MAXQDA 2018. In order to ensure the consistency of the data analysis, the data were analyzed by another field expert and the 92% consensus was tried to be reached by using the consistency formula. Results: Participant opinions consist of benefiting status from AAC, opinions on the importance of AAC, preferred case groups and reasons for AAC implementation, opinions on current best practice understanding on communication and language intervention/use of AAC, opinions on current working conditions on AAC practices, opinions on the limitations of the use of AAC in communication and language intervention and recommendations for ensuring effective use of AAC themes. Conclusions: The results of the study show that supporting individuals who can benefit from AAC in the context of intervention services for communication disorders requires great effort. In addition, SLTs stated that they strongly believed in AAC and its potential value for individuals with communication disorders, but did not have sufficient self-confidence about their current or developing skills in this area. It is also seen that clinicians need training and support from employers, professional or government agencies that set policies and standards to achieve their AAC related goals.